Two new species of Pelophryne (Anura: Bufonidae) from Gunung Murud, Sarawak (northwestern Borneo). - Das, I. (National University of Singapore, 2008)
Two new species of bufonids of the genus Pelophryne are described from the Gunung Murud region of northern Sarawak State, Malaysian Borneo. Pelophryne murudensis, new species, adult males to 25.6 mm SVL, fi nger tips not wider than basal phalanges, fi nger tips not wider than basal phalanges, snout oblique, absence of a free phalange on Finger I, subarticular tubercles distinct, mandibular spines absent and nuptial pads absent. Pelophryne linanitensis, new species, adult males to 18.6 mm SVL, fi nger tips not wider than basal phalanges, snout vertical, absence of a free phalange on Finger I, webbing to tip of Toe V, subarticular tubercles distinct, mandibular spines absent, presence of a dark hour-glass pattern on dorsum and pale fl ank stripes